GOVERNMENT SUPPORT TO BUSINESS INNOVATION POTENTIAL: FUNDING MECHANISM AND IMPETUS FOR GROWTH UNDER MARTIAL LAW - Zaburanna, Lesia V.; Yarmolenko, Yuliia O. (Journal of Strategic Economic Research, 2022)
The article addresses the issues of finding pathways to foster the national economic growth against the martial law context. It is noted that with the start of hostilities in Ukraine, all business processes and the normal functioning of the economy slowed down, in particular, this refers to innovative activities, research and development, intellectual property and the overall national innovation potential. The paper observes that there is an objective need to build an effective innovation funding mechanism which will provide an opportunity to generate accumulated assets in the key priority areas to enhance the innovation potential of Ukrainian businesses. It is emphasized that this mechanism of financing innovations should rely upon the following fundamental principles: targeted focus towards financial vectoring; verified justification and legal support to primary sources of assets; a polystructural character of asset sources; financial depth and breadth; adaptability of the funding system to wartime conditions to gain synergy from using its constituent elements. Based on international best practice, it is argued that business innovation support and innovation effectiveness rest largely on the funding timeliness and target focus. The study suggests that the innovation funding mechanism will create favourable environment to ensure prompt and efficient implementation of innovation processes in all areas of business. In the context of this study, government support to business innovation potential is viewed as part of the overall business strategy in strengthening and boosting innovation potential for the future. According to the research findings, the key impetus to support innovations under martial law are the following: motivational incentives for business units and companies engaged in investing in research and development of innovative enterprises; encouraging the creation of research centres; promoting innovative and technological growth zones; active assistance in facilitating modernization of innovative businesses; government grant initiatives and preferential lending programmes; innovation export support and promotion; in-depth support to innovative public procurement schemes; making use of a special tax regime for intellectual property products which contributes to shaping a favourable tax rate on income from intellectual property commercialization. The study offers important implications for further research in developing an effective framework to boost innovations which will enhance collaboration and increase the efficiency of research, industrial, financial, innovative and personnel potentials. Ultimately, this will have a positive effect on encouraging global cooperation in the vector of innovative activities, will ensure technology transfer and innovation commercialization, as well as contribute to increasing the share of innovative products in world markets. The implementation of the above priority objectives will help Ukraine to respond to modern challenges, overcome the current crisis and spur further economic growth.